2015
DOI: 10.1007/s11420-015-9468-2
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Derotation in Adolescent Idiopathic Scoliosis: a Novel Technique Measuring Postoperative Vertebral Rotation by Pedicle Screw Position

Abstract: Background: Current methods of measuring vertebral rotation by plain radiographs rely on anatomic landmarks that are not present in the postoperative spine or require advanced imaging. Furthermore, there are few studies on the incidence of crankshaft with modern pedicle instrumentation. Questions/Purposes: We sought to (1) describe and validate a method of vertebral rotation measurement using plain radiographs and (2) measure postoperative rotation in a series of patients treated for adolescent idiopathic scol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
(50 reference statements)
1
5
0
Order By: Relevance
“…Another study using the separation between the rods on a lateral radiograph to estimate the rotation using a trigonometric function also yielded results similar to those obtained with CT (r=0.84) 22) , although the distance between the rods is difficult to measure at the PS level due to the screw heads, and a consistent rod width is assumed. In contrast, Bjerke et al 8) reported that the average difference between the axial rotation measured on CT and that measured using radiographs was 3.3±1.9°, which is similar to the difference reported in the current study in which no assumptions regarding screw length or rod width are made. This method is accurate and reproducible in patients in whom a PS is inserted.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Another study using the separation between the rods on a lateral radiograph to estimate the rotation using a trigonometric function also yielded results similar to those obtained with CT (r=0.84) 22) , although the distance between the rods is difficult to measure at the PS level due to the screw heads, and a consistent rod width is assumed. In contrast, Bjerke et al 8) reported that the average difference between the axial rotation measured on CT and that measured using radiographs was 3.3±1.9°, which is similar to the difference reported in the current study in which no assumptions regarding screw length or rod width are made. This method is accurate and reproducible in patients in whom a PS is inserted.…”
Section: Discussionsupporting
confidence: 83%
“…A previous study reported that the evaluation of vertebral rotation after posterior fusion using the inverse trigonometric function method is a more sensitive determination of CSP than changes in the Cobb angle 8) . This previous study defined CSP as a Cobb angle >10°, which occurred in 4.6% of patients and a vertebral rotation >5° occurred in 19.2% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations